TRANSFORMASI EKONOMI RUMAH TANGGA MELALUI PENGOLAHAN SAMPAH DOMESTIK, PENDAMPINGAN PRODUK BERBASIS SAMPAH - Lopes Amaral, Maria Augustin; Manehat, Beatrix Yunarti; Tukan, Gerardus D.; Boelan, Erly Grizca; Ang, Clarisa Margaretha; Gani, Elisabeth Adelia Merdekawati; Setiawan, Apolinaris; Gokok, Gaspar Antonius Padua Rapok; Bria, Kristina; Boikh, Ananda Oky Mekel M. (LPPM Universitas Bina Bangsa, 2024)
Introduction: Waste management in RT 041 Liliba is still ineffective, with many residents not separating organic and inorganic waste, which has an impact on the environment. Objective: To increase community awareness and skills in waste management through the establishment of a Waste Bank and training in making organic fertilizer. Research Method: Conducting socialization, practical training, and developing applications to monitor waste management and savings at the Waste Bank, introducing the RT 041 Liliba Waste Bank and liquid fertilizer products through social media. Results: The community succeeded in attracting the interest of 50 potential consumers for organic fertilizer products, and the application made it easier to monitor waste and savings. Conclusion: This program not only increases awareness of the importance of waste separation, but also opens up new economic opportunities, supporting environmental sustainability in RT 041 Liliba